Spontaneous Thoracic Spinal Epidural Hematoma: A Rare Cause of Paraparesis - Kaushal, Prashant; Jha, Rajiv; Kumar, Pawan; Sharma, Gopal R (Nepal Journal of Neuroscience, 2017)
Abstract available with full text. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 32-35